A hierarchical layered silicon carbide ceramic and its preparation method
Patent Information
- Application Number
- CN202611178643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-09-01
AI Technical Summary
[0004]但是,现有技术仍难以同时兼顾结构可控性和增韧效果
Smart Images

Figure CN122667934A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of advanced ceramic material preparation technology, specifically relating to a hierarchical layered silicon carbide ceramic and its preparation method. Background Technology
[0002] Silicon carbide ceramics possess characteristics such as high temperature resistance, corrosion resistance, oxidation resistance, and high strength, making them widely used in semiconductor etching components, new energy power battery kilns, environmental filtration, and high-temperature wear-resistant components. As the service environments of related equipment become increasingly harsh, silicon carbide ceramics not only need to withstand high temperatures and corrosion but also need to maintain stability and reliability under thermal cycling, mechanical shock, and complex loads. However, ordinary silicon carbide ceramics are relatively brittle and have low fracture toughness. Once cracks form, they tend to propagate rapidly, potentially leading to sudden component fracture. Therefore, improving the crack propagation resistance and service reliability of silicon carbide ceramics is a crucial practical application requirement.
[0003] Currently, various technical approaches have been proposed to address the brittleness of silicon carbide ceramics. For example, the ceramic microstructure can be improved by adding reinforcing phases, adjusting sintering aids, and optimizing the sintering process; layered or composite structures can be constructed to deflect and branch cracks during propagation, thereby consuming more fracture energy; additive manufacturing can improve the forming precision of complex ceramic components; and reaction sintering can improve the bonding state and internal structure of ceramic materials. These methods have improved the mechanical properties of silicon carbide ceramics to some extent.
[0004] However, existing technologies still struggle to simultaneously achieve structural controllability and toughening effects. While some layered ceramics can form interlayer structures, the interlayer scale and interface state are difficult to control stably, limiting their ability to regulate crack propagation paths. Although some additive manufacturing methods are beneficial for forming complex shapes, the structural fit between different layers and the subsequent microstructure changes after sintering remain difficult to coordinate. While some composite modification or reaction sintering methods can improve the internal microstructure of ceramics, the distribution and morphology of reinforcing or newly formed phases in the material are difficult to control, resulting in unstable toughening effects. Therefore, there is still room for improvement in the fine-tuning of the structure, stable interface bonding, and enhanced fracture toughness of existing silicon carbide ceramics.
[0005] Therefore, developing a silicon carbide ceramic preparation method that can simultaneously achieve complex component forming, stable construction of layered structures, reliable interface bonding, and effective control of crack propagation has become an urgent technical problem to be solved in this field. This method should be able to improve the fracture toughness and resistance to brittle fracture of silicon carbide ceramics while maintaining their high-temperature resistance and corrosion resistance, in order to meet the long-term reliable service requirements of key ceramic components in semiconductors, new energy sources, high-temperature kilns, and other harsh operating conditions. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention proposes a hierarchical layered silicon carbide ceramic and its preparation method. This invention involves separately preparing a matrix layer slurry containing first-layer flake powder and an interface layer slurry containing flake graphene. The layers are then spread layer by layer using a doctor blade and alternately printed using 3D photocuring. Following drying, debinding, and embedded silicon reaction sintering, this provides an innovative solution for improving the fracture toughness and structural reliability of silicon carbide ceramics.
[0007] The first objective of this invention is achieved through the following technical solution:
[0008] A method for preparing hierarchical layered silicon carbide ceramics includes the following steps:
[0009] (1) A first silicon carbide mixed powder with a mass ratio of 3:7 to 11:9 is mixed with a first liquid phase composition to obtain a matrix layer slurry;
[0010] (2) The second silicon carbide mixed powder with a mass ratio of 3:7 to 2:3 is mixed with the second liquid phase composition to obtain an interface layer slurry;
[0011] (3) The substrate slurry and the interface slurry are spread layer by layer using a scraper, and then 3D photocuring is performed to print layer by layer alternately to form at least one hundred layered repeating units. Each layered repeating unit includes a substrate layer and an interface layer arranged alternately along the thickness direction to obtain a graded layered ceramic blank.
[0012] (4) The graded layered ceramic green body is dried and degreased to obtain a degreased ceramic green body;
[0013] (5) The degreased ceramic blank is embedded in silicon powder and sintered under vacuum at 1650-1750℃ to obtain graded layered silicon carbide ceramic.
[0014] Wherein, the first silicon carbide mixed powder includes silicon carbide and a first sheet-like powder, wherein the first sheet-like powder is any one or two of sheet-like boron nitride and sheet-like alumina.
[0015] In the first silicon carbide mixed powder, the first flake powder is 1-3 parts by weight, with silicon carbide as 100 parts by weight;
[0016] The second silicon carbide mixed powder comprises silicon carbide and sheet-like graphene;
[0017] In the second silicon carbide mixed powder, based on 100 parts by mass of silicon carbide, the sheet-like graphene comprises 0.5-2 parts by mass;
[0018] The thickness of the sheet-like graphene is 100-400 nm, and the average sheet diameter is 2-5 μm;
[0019] Both the first liquid phase composition and the second liquid phase composition contain a photosensitive resin, a dispersant, and a photoinitiator;
[0020] In any of the layered repeating units, the thickness ratio of the matrix layer to the interface layer is (2-5):1.
[0021] Preferably, the single-layer cured thickness of the substrate layer is 30-60 μm.
[0022] More preferably, the single-layer cured thickness of the substrate layer is 30-50 μm.
[0023] Preferably, in step (1), the first silicon carbide mixed powder further comprises aluminum oxide and yttrium oxide; based on 100 parts by mass of silicon carbide in the first silicon carbide mixed powder, the aluminum oxide comprises 4-8 parts by mass and the yttrium oxide comprises 6-12 parts by mass.
[0024] More preferably, in step (1), based on 100 parts by mass of silicon carbide in the first silicon carbide mixed powder, the alumina is 5-7 parts by mass, the yttrium oxide is 7-9 parts by mass, and the first flake powder is 1-2 parts by mass.
[0025] Preferably, in step (2), the second silicon carbide mixed powder further comprises aluminum oxide and yttrium oxide; based on 100 parts by mass of silicon carbide in the second silicon carbide mixed powder, the aluminum oxide comprises 4-8 parts by mass and the yttrium oxide comprises 6-12 parts by mass.
[0026] More preferably, in step (2), based on 100 parts by mass of silicon carbide in the second silicon carbide mixed powder, the alumina is 7-9 parts by mass, the yttrium oxide is 9-11 parts by mass, and the sheet graphene is 0.8-1.2 parts by mass.
[0027] Preferably, in steps (1) and (2), the average particle size of the silicon carbide is 2-40 μm.
[0028] More preferably, in steps (1) and (2), the average particle size of the silicon carbide is 10-20 μm.
[0029] Preferably, in steps (1) and (2), the photosensitive resin is any one or more of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, bisphenol A epoxy acrylate, toluene 2,4-diisocyanate, and hydroxyethyl acrylate.
[0030] More preferably, the photosensitive resin is a mixture of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate.
[0031] More preferably, the volume ratio of the 1,6-hexanediol diacrylate to the trimethylolpropane triacrylate is (5-8):(1-4).
[0032] Preferably, in steps (1) and (2), the dispersant is any one or more of polypropylene glycol, polyphosphate ester and modified acrylic copolymer.
[0033] Preferably, in steps (1) and (2), the photoinitiator is any one or more of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methylphenylacetone, and 1-hydroxycyclohexylphenyl ketone.
[0034] Preferably, in step (1), based on a total mass of 100 parts by mass of the first silicon carbide mixed powder, photosensitive resin, dispersant and photoinitiator in the matrix layer slurry, the first silicon carbide mixed powder is 30-55 parts by mass, the dispersant is 0.5-3 parts by mass, the photoinitiator is 0.1-1 parts by mass, and the photosensitive resin is the balance.
[0035] More preferably, in step (1), based on a total mass of 100 parts by mass of the first silicon carbide mixed powder, photosensitive resin, dispersant and photoinitiator in the matrix layer slurry, the first silicon carbide mixed powder is 45-49 parts by mass, the dispersant is 2-3 parts by mass, the photoinitiator is 0.3-0.7 parts by mass, and the photosensitive resin is the balance.
[0036] Preferably, in step (2), based on a total mass of 100 parts by mass of the second silicon carbide mixed powder, photosensitive resin, dispersant and photoinitiator in the interface layer slurry, the second silicon carbide mixed powder is 30-40 parts by mass, the dispersant is 0.5-2 parts by mass, the photoinitiator is 0.1-1 parts by mass, and the photosensitive resin is the balance.
[0037] More preferably, in step (2), based on a total mass of 100 parts by mass of the second silicon carbide mixed powder, photosensitive resin, dispersant and photoinitiator in the interface layer slurry, the second silicon carbide mixed powder is 36-40 parts by mass, the dispersant is 1-1.8 parts by mass, the photoinitiator is 0.4-0.8 parts by mass, and the photosensitive resin is the balance.
[0038] Preferably, the matrix slurry further includes one or more additives selected from defoamers, leveling agents, coupling agents, diluents, and plasticizers.
[0039] Preferably, the interface layer slurry further includes one or more additives selected from defoamers, leveling agents, coupling agents, diluents, and plasticizers.
[0040] Preferably, in step (1), the mixing of the first silicon carbide mixed powder and the first liquid phase composition is ball milling; in step (2), the mixing of the second silicon carbide mixed powder and the second liquid phase composition is ball milling.
[0041] More preferably, in step (1), the ball milling speed of the first silicon carbide mixed powder and the first liquid phase composition is 200-400 rpm, and the ball milling time is 5-10 h; in step (2), the ball milling speed of the second silicon carbide mixed powder and the second liquid phase composition is 150-300 rpm, and the ball milling time is 3-6 h.
[0042] More preferably, in step (1), the ball milling speed of the first silicon carbide mixed powder and the first liquid phase composition is 250-300 rpm, and the ball milling time is 6-8 h; in step (2), the ball milling speed of the second silicon carbide mixed powder and the second liquid phase composition is 180-220 rpm, and the ball milling time is 4-5 h.
[0043] Preferably, in step (3), the 3D photopolymerization layer-by-layer alternating printing is performed using a DLP printing device.
[0044] More preferably, in step (3), the matrix layer slurry and the interface layer slurry are placed in different liquid tanks of the DLP printing equipment, the ceramic three-dimensional CAD model data is imported, and the printing is performed layer by layer according to the preset layer parameters and scanning path data.
[0045] Preferably, in step (3), the scraper spreads the substrate slurry or the interface slurry along the forming surface direction.
[0046] More preferably, in step (3), the scraper spreads the substrate slurry or the interface slurry and generates a shearing action along the surface direction, so that the flaky powder in the slurry tends to be oriented and arranged along the surface direction.
[0047] Preferably, in step (3), the curing thickness of the substrate layer is 30-50 μm and the curing thickness of the interface layer is 10-20 μm.
[0048] More preferably, in step (3), the curing thickness of the substrate layer is 38-42 μm and the curing thickness of the interface layer is 10-14 μm.
[0049] Preferably, in step (3), during the alternating layer-by-layer 3D photocuring printing, the intensity of the ultraviolet light source used for the substrate slurry is 10-30 mW / cm². 2The curing time for a single layer is 9-20 seconds; the intensity of the ultraviolet light source used for the interface layer slurry is 10-20 mW / cm². 2 The curing time for a single layer is 4-6 seconds.
[0050] More preferably, in step (3), during the alternating layer-by-layer 3D photocuring printing, the intensity of the ultraviolet light source used for the substrate slurry is 16-20 mW / cm². 2 The curing time for a single layer is 9-11 seconds; the intensity of the ultraviolet light source used for the interface layer slurry is 18-20 mW / cm². 2 The curing time for a single layer is 4-4.5 seconds.
[0051] Preferably, in step (4), the drying temperature is 80-120℃ and the drying time is 10-20 h.
[0052] More preferably, in step (4), the drying temperature is 100-110℃ and the drying time is 12-16 h.
[0053] Preferably, in step (4), the degreasing is carried out under a nitrogen protective atmosphere.
[0054] More preferably, in step (4), the heating rate of the degreasing process is 0.1-0.3℃ / min.
[0055] More preferably, in step (4), the degreasing includes heating to 750-850°C at a heating rate of 0.2-0.3°C / min.
[0056] Preferably, in step (5), the silicon powder is high-purity silicon powder.
[0057] Preferably, in step (5), the reaction sintering time is 1-4 h.
[0058] More preferably, in step (5), the reaction sintering includes heating to 1680-1720℃ at a heating rate of 1.2-1.8℃ / min and holding at that temperature for 2.5-3.5 h.
[0059] This method introduces a first sheet-like powder into the matrix layer slurry and localizes sheet-like graphene into the interface layer slurry. Layer-by-layer spreading with a doctor blade and alternating 3D photopolymerization printing ensures the matrix and interface layers are alternately arranged along the thickness direction, while simultaneously giving the sheet-like powder a tendency to align along the layer direction. After drying and degreasing, the ceramic green body reacts with external silicon powder during the embedded silicon reaction sintering process. Due to the layered structure of the sheet-like graphene itself, the in-situ transformation of the sheet-like graphene in the interface layer can form a sheet-like silicon carbide structure that retains its sheet-like morphology and possesses an internal layered structure. Thus, the resulting ceramic forms a hierarchical layered structure with alternating matrix and interface layers, oriented sheet-like powder, and localized layered silicon carbide distribution in the interface layer. This structure enables cracks to deflect between the matrix layer and the interface layer, and further induces crack bifurcation, bridging, and energy dissipation through the lamellar powder and the lamellar silicon carbide structure with internal layered structure, thereby achieving the technical effect of improving the fracture toughness and structural reliability of silicon carbide ceramics.
[0060] The second objective of this invention is achieved through the following technical solution:
[0061] A hierarchical layered silicon carbide ceramic is prepared by any of the preparation methods described above.
[0062] Preferably, the fracture toughness of the hierarchical layered silicon carbide ceramic is 7-10 MPa·m. 1 / 2 .
[0063] Preferably, the flexural strength of the graded layered silicon carbide ceramic is 280-330 MPa.
[0064] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0065] 1. This invention uses alternating printing of matrix layer slurry and interface layer slurry, and introduces first sheet-like powder in the matrix layer and sheet-like graphene in the interface layer, so that the resulting ceramic can form a hierarchical layered structure with alternating matrix layer and interface layer, providing a structural basis for crack deflection and fracture energy dissipation.
[0066] 2. This invention uses a scraper to spread the slurry layer by layer. During the spreading process, the scraper can promote the arrangement of sheet-like powder along the layer direction, so that sheet-like boron nitride or sheet-like alumina and sheet-like graphene can better participate in the construction of the layered structure, thereby enhancing crack deflection, bifurcation and bridging effects.
[0067] 3. This invention utilizes embedded silicon reaction sintering to allow sheet-like graphene in the interface layer to react in situ with metallic silicon, generating a sheet-like silicon carbide structure that retains its sheet-like morphology and possesses an internal layered structure. This sheet-like silicon carbide is then concentrated within the interface layer. This structure, on the one hand, enhances crack deflection, bifurcation, and bridging effects by utilizing the sheet-like morphology and internal layered structure of the silicon carbide; on the other hand, it improves the interface layer's ability to control crack propagation paths, thereby further enhancing the fracture toughness and structural reliability of silicon carbide ceramics.
[0068] 4. The present invention controls the ratio of the curing thickness of the single layer of the matrix layer to the curing thickness of the single layer of the interface layer to be (2-5):1, so that the interface layer can be distributed in a thinner form between the matrix layers, which is beneficial to improving the frequency of interlayer crack modulation, while taking into account the stability of the layered structure and the overall load-bearing reliability.
[0069] 5. This invention, through the optimal combination of photosensitive resin, dispersant, photoinitiator, sintering aid, ball milling, photocuring printing, drying, degreasing and reaction sintering, makes the matrix layer slurry and interface layer slurry suitable for alternating layer-by-layer forming, and is conducive to obtaining hierarchical layered silicon carbide ceramics with high fracture toughness and structural reliability. It is suitable for ceramic parts in semiconductors, new energy, high-temperature kiln furniture and other harsh working conditions. Attached Figure Description
[0070] Figure 1 The schematic diagram of the structure of the hierarchical layered silicon carbide ceramic provided in this application is shown, wherein 1 is the matrix layer, 2 is the interface layer, 3 is the first sheet-like powder, 4 is sheet-like graphene, and 5 is a sheet-like silicon carbide structure with an internal layered structure.
[0071] Figure 2 A scanning electron microscope image of a cross section of the hierarchical layered silicon carbide ceramic preform prepared in Example 1;
[0072] Figure 3 A scanning electron microscope image of the interface layer region of the hierarchical layered silicon carbide ceramic prepared in Example 1;
[0073] Figure 4 The image shows a scanning electron microscope image of sheet-like silicon carbide with an internal layered structure in the hierarchical layered silicon carbide ceramic prepared in Example 1. Detailed Implementation
[0074] The following will provide a clear and complete description of the concept, specific structure, and technical effects of the present invention in conjunction with the embodiments and accompanying drawings, so as to fully understand the purpose, solution, and effects of the present invention. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0075] The materials used in the embodiments and comparative examples of this invention are described below:
[0076] Silicon carbide powder: average particle size 10μm, purchased from Shandong Yamada New Materials Research Co., Ltd.
[0077] Plate-shaped boron nitride: with an average plate diameter of 5 μm, a thickness of 200 nm, and a purity of 99%, purchased from Shandong Jingyi New Materials Co., Ltd.
[0078] Flake-shaped alumina: average flake diameter 3 μm, thickness 400 nm, purity 99%, purchased from Lianrui New Materials;
[0079] Sheet graphene: average sheet diameter 3μm, thickness 200 nm, purity 99%, purchased from Kaina Graphene.
[0080] Carbon black: average particle size 5μm, purity 99%, purchased from Cabot.
[0081] 1,6-Hexanediol diacrylate: 99% purity, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0082] Trimethylolpropane triacrylate: 99% purity, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0083] Polypropylene glycol: number average molecular weight 5000, purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0084] Diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide: 99% purity, purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0085] High-purity silicon powder: 99% purity, average particle size 10μm, purchased from Hoshine Silicon Industry.
[0086] Example 1
[0087] The method for preparing the hierarchical layered silicon carbide ceramic in Example 1 includes the following steps:
[0088] (1) Weigh 100 parts of silicon carbide powder, 6 parts of alumina, 8 parts of yttrium oxide and 1.5 parts of flake boron nitride according to the internal mass ratio of the first silicon carbide mixed powder, and mix them to obtain the first silicon carbide mixed powder.
[0089] Based on a total mass of 100 parts by mass of the matrix layer slurry, 47 parts by mass of the first silicon carbide mixed powder, 50 parts by mass of the photosensitive resin, 2.5 parts by mass of polypropylene glycol, and 0.5 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 6:3. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the first liquid phase composition. The first silicon carbide mixed powder and the first liquid phase composition were ball-milled at 200 rpm for 6 h to obtain the matrix layer slurry.
[0090] (2) Weigh 100 parts of silicon carbide powder, 8 parts of alumina, 10 parts of yttrium oxide and 1 part of sheet graphene according to the internal mass ratio of the second silicon carbide mixed powder, and mix them to obtain the second silicon carbide mixed powder.
[0091] Based on a total mass of 100 parts by mass of the interface layer slurry, 38 parts by mass of the second silicon carbide mixed powder, 60 parts by mass of the photosensitive resin, 1.4 parts by mass of polypropylene glycol, and 0.6 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 2:1. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the second liquid phase composition. The second silicon carbide mixed powder and the second liquid phase composition were ball-milled at 200 rpm for 4 h to obtain the interface layer slurry.
[0092] (3) Establish a 3D CAD model of the ceramic component to be prepared, set the layering parameters and scanning path, and place the matrix layer slurry and interface layer slurry in different liquid tanks of the DLP printing equipment. Use a scraper to spread the matrix layer slurry or interface layer slurry to be printed layer by layer along the forming layer direction, and perform 3D photocuring on the spread slurry to print layer by layer alternately, so that the matrix layer slurry and interface layer slurry are cured to form matrix layer and interface layer alternately arranged along the thickness direction. One matrix layer and one interface layer constitute a set of layered repeating units, and a total of 1000 sets of layered repeating units are printed along the thickness direction. The intensity of the ultraviolet light source used for the matrix layer slurry is 18 mW / cm. 2 The curing time for a single layer is 10 s, and the curing thickness of a single layer is 40 μm; the intensity of the ultraviolet light source used for the interface layer slurry is 20 mW / cm². 2 The curing time for a single layer was 4 s, and the curing thickness of a single layer was 12 μm, resulting in a graded layered ceramic preform.
[0093] (4) The graded layered ceramic green body was dried at 110℃ for 12 h, and then degreased under a nitrogen protective atmosphere. The temperature was increased to 800℃ at a heating rate of 0.25℃ / min to obtain the degreased ceramic green body.
[0094] (5) The degreased ceramic blank was embedded in high-purity silicon powder, heated to 1700℃ at a heating rate of 1.5℃ / min and held for 4 h to carry out reaction sintering, and the graded layered silicon carbide ceramic of Example 1 was obtained.
[0095] Example 2
[0096] The difference between the graded layered silicon carbide ceramic of Example 2 and that of Example 1 lies in the type of the first sheet-like powder in step (1), while the other steps are the same as those of Example 1:
[0097] (1) Weigh 100 parts of silicon carbide powder, 6 parts of alumina, 8 parts of yttrium oxide and 1.5 parts of flake alumina according to the internal mass ratio of the first silicon carbide mixed powder, and mix them to obtain the first silicon carbide mixed powder.
[0098] Based on a total mass of 100 parts by mass of the matrix layer slurry, 47 parts by mass of the first silicon carbide mixed powder, 50 parts by mass of the photosensitive resin, 2.5 parts by mass of polypropylene glycol, and 0.5 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 6:3. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the first liquid phase composition. The first silicon carbide mixed powder and the first liquid phase composition were ball-milled at 200 rpm for 6 h to obtain the matrix layer slurry.
[0099] (2-5) Following the steps (2-5) of Example 1, the hierarchical layered silicon carbide ceramic of Example 2 is obtained.
[0100] Example 3
[0101] The difference between the hierarchical layered silicon carbide ceramic of Example 3 and that of Example 1 lies in the different curing thicknesses of the substrate layer and the interface layer in step (3). The other steps are the same as those of Example 1.
[0102] (1-2) Following the steps (1-2) of Example 1, the matrix layer slurry and the interface layer slurry are obtained respectively.
[0103] (3) Establish a 3D CAD model of the ceramic component to be prepared, set the layering parameters and scanning path, and place the matrix layer slurry and interface layer slurry in different liquid tanks of the DLP printing equipment. Use a scraper to spread the matrix layer slurry or interface layer slurry to be printed layer by layer along the forming layer direction, and perform 3D photocuring on the spread slurry to print layer by layer alternately, so that the matrix layer slurry and interface layer slurry are cured to form matrix layer and interface layer alternately arranged along the thickness direction. One matrix layer and one interface layer constitute a set of layered repeating units, and a total of 500 sets of layered repeating units are printed along the thickness direction. The intensity of the ultraviolet light source used for the matrix layer slurry is 18 mW / cm. 2 The curing time for a single layer is 12 s, and the curing thickness of a single layer is 50 μm; the intensity of the ultraviolet light source used for the interface layer slurry is 20 mW / cm². 2 The curing time for a single layer was 4 s, and the curing thickness of a single layer was 10 μm, resulting in a graded layered ceramic preform.
[0104] (4-5) Following the steps (4-5) of Example 1, the hierarchical layered silicon carbide ceramic of Example 3 is obtained.
[0105] Comparative Example 1
[0106] The difference between the silicon carbide ceramic sample of Comparative Example 1 and Example 1 lies in the different single-layer curing thickness of the interface layer in step (3). The other steps are the same as those in Example 1.
[0107] (1-2) Following the steps (1-2) of Example 1, the matrix layer slurry and the interface layer slurry are obtained respectively.
[0108] (3) Establish a 3D CAD model of the ceramic component to be prepared, set the layering parameters and scanning path, and place the matrix layer slurry and interface layer slurry in different liquid tanks of the DLP printing equipment. Use a scraper to spread the matrix layer slurry or interface layer slurry to be printed layer by layer along the forming layer direction, and perform 3D photocuring on the spread slurry to print layer by layer alternately, so that the matrix layer slurry and interface layer slurry are cured to form matrix layer and interface layer alternately arranged along the thickness direction. One matrix layer and one interface layer constitute a set of layered repeating units, and a total of 1000 sets of layered repeating units are printed along the thickness direction. The intensity of the ultraviolet light source used for the matrix layer slurry is 18 mW / cm. 2 The curing time for a single layer is 10 s, and the curing thickness of a single layer is 40 μm; the intensity of the ultraviolet light source used for the interface layer slurry is 20 mW / cm². 2 The curing time for a single layer was 4 seconds, and the curing thickness of a single layer was 30 μm, resulting in a ceramic green body.
[0109] (4-5) Following the steps (4-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 1 was obtained.
[0110] Comparative Example 2
[0111] The difference between the silicon carbide ceramic sample of Comparative Example 2 and Example 1 lies in the different thickness of the single-layer curing of the interface layer in step (3). The other steps are the same as those in Example 1.
[0112] (1-2) Following the steps (1-2) of Example 1, the matrix layer slurry and the interface layer slurry are obtained respectively.
[0113] (3) Establish a 3D CAD model of the ceramic component to be prepared, set the layering parameters and scanning path, and place the matrix layer slurry and interface layer slurry in different liquid tanks of the DLP printing equipment. Use a scraper to spread the matrix layer slurry or interface layer slurry to be printed layer by layer along the forming layer direction, and perform 3D photocuring on the spread slurry to print layer by layer alternately, so that the matrix layer slurry and interface layer slurry are cured to form matrix layer and interface layer alternately arranged along the thickness direction. One matrix layer and one interface layer constitute a set of layered repeating units, and a total of 800 sets of layered repeating units are printed along the thickness direction. The intensity of the ultraviolet light source used for the matrix layer slurry is 18 mW / cm. 2 The curing time for a single layer is 10 s, and the curing thickness of a single layer is 40 μm; the intensity of the ultraviolet light source used for the interface layer slurry is 20 mW / cm². 2 The curing time for a single layer was 4 s, and the curing thickness of a single layer was 40 μm, resulting in a ceramic green body.
[0114] (4-5) Following the steps (4-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 2 was obtained.
[0115] Comparative Example 3
[0116] The difference between the silicon carbide ceramic sample of Comparative Example 3 and Example 1 lies in the different thickness of the single-layer curing of the interface layer in step (3). The other steps are the same as those in Example 1.
[0117] (1-2) Following the steps (1-2) of Example 1, the matrix layer slurry and the interface layer slurry are obtained respectively.
[0118] (3) Establish a 3D CAD model of the ceramic component to be prepared, set the layering parameters and scanning path, and place the matrix layer slurry and interface layer slurry in different liquid tanks of the DLP printing equipment. Use a scraper to spread the matrix layer slurry or interface layer slurry to be printed layer by layer along the forming layer direction, and perform 3D photocuring on the spread slurry to print layer by layer alternately, so that the matrix layer slurry and interface layer slurry are cured to form matrix layer and interface layer alternately arranged along the thickness direction. One matrix layer and one interface layer constitute a set of layered repeating units, and a total of 800 sets of layered repeating units are printed along the thickness direction. The intensity of the ultraviolet light source used for the matrix layer slurry is 18 mW / cm. 2The curing time for a single layer is 10 s, and the curing thickness of a single layer is 48 μm; the intensity of the ultraviolet light source used for the interface layer slurry is 20 mW / cm². 2 The curing time for a single layer was 4 s, and the curing thickness of a single layer was 8 μm, resulting in a ceramic green body.
[0119] (4-5) Following the steps (4-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 3 was obtained.
[0120] Comparative Example 4
[0121] The difference between the silicon carbide ceramic sample of Comparative Example 4 and Example 1 is that the type of carbon source used in the interface layer in step (2) is different; the other steps are the same as in Example 1.
[0122] (1) Follow the steps (1) of Example 1 to obtain the matrix layer slurry.
[0123] (2) Weigh 100 parts of silicon carbide powder, 8 parts of alumina, 10 parts of yttrium oxide and 1 part of carbon black according to the internal mass ratio of the second silicon carbide mixed powder, and mix them to obtain the second silicon carbide mixed powder.
[0124] Based on a total mass of 100 parts by mass of the interface layer slurry, 38 parts by mass of the second silicon carbide mixed powder, 60 parts by mass of the photosensitive resin, 1.4 parts by mass of polypropylene glycol, and 0.6 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 3:1. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the second liquid phase composition. The second silicon carbide mixed powder and the second liquid phase composition were ball-milled at 200 rpm for 4 h to obtain the interface layer slurry.
[0125] (3-5) Following the steps (3-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 4 was obtained.
[0126] Comparative Example 5
[0127] The difference between the silicon carbide ceramic sample of Comparative Example 5 and Example 1 is that step (3) does not involve alternating printing of the substrate layer slurry and the interface layer slurry; the other steps are the same as in Example 1.
[0128] (1) Follow the steps (1) of Example 1 to obtain the matrix layer slurry.
[0129] (2) Follow the steps (2) of Example 1 to obtain the interface layer slurry.
[0130] (3) The matrix layer slurry obtained in step (1) and the interface layer slurry obtained in step (2) are mixed evenly according to the printing volume ratio of the matrix layer and the interface layer in Example 1 to obtain a single mixed slurry. The single mixed slurry is placed in the liquid tank of the DLP printing equipment, the ceramic three-dimensional CAD model data is imported, and 3D photopolymerization printing is performed according to the preset layer parameters and scanning path data to obtain the ceramic green body.
[0131] (4-5) Following the steps (4-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 5 was obtained.
[0132] Comparative Example 6
[0133] The difference between the silicon carbide ceramic sample of Comparative Example 6 and Example 1 lies in the different distribution patterns of sheet graphene in steps (1) and (2). The other steps are the same as in Example 1:
[0134] (1) Weigh 100 parts of silicon carbide powder, 6 parts of alumina, 8 parts of yttrium oxide, 1.5 parts of sheet boron nitride and 0.2 parts of sheet graphene according to the internal mass ratio of the first silicon carbide mixed powder, and mix them to obtain the first silicon carbide mixed powder.
[0135] Based on a total mass of 100 parts by mass of the matrix layer slurry, 47 parts by mass of the first silicon carbide mixed powder, 50 parts by mass of the photosensitive resin, 2.5 parts by mass of polypropylene glycol, and 0.5 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 6:3. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the first liquid phase composition. The first silicon carbide mixed powder and the first liquid phase composition were ball-milled at 200 rpm for 6 h to obtain the matrix layer slurry.
[0136] (2) Weigh 100 parts of silicon carbide powder, 8 parts of alumina, 10 parts of yttrium oxide and 0.2 parts of sheet graphene according to the internal mass ratio of the second silicon carbide mixed powder, and mix them to obtain the second silicon carbide mixed powder.
[0137] Based on a total mass of 100 parts by mass of the interface layer slurry, 38 parts by mass of the second silicon carbide mixed powder, 60 parts by mass of the photosensitive resin, 1.4 parts by mass of polypropylene glycol, and 0.6 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 3:1. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the second liquid phase composition. The second silicon carbide mixed powder and the second liquid phase composition were ball-milled at 200 rpm for 4 h to obtain the interface layer slurry.
[0138] (3-5) Following the steps (3-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 6 was obtained.
[0139] In Comparative Example 6, the total amount of sheet graphene added was comparable to that in Example 1, but the sheet graphene was no longer added to the interface layer slurry in a concentrated manner, but was added to the matrix layer slurry and the interface layer slurry separately.
[0140] Comparative Example 7
[0141] The difference between the silicon carbide ceramic sample of Comparative Example 7 and Example 1 lies in the different lamellar reinforcing phase used in the interface layer in step (2). The other steps are the same as in Example 1:
[0142] (1) Follow the steps (1) of Example 1 to obtain the matrix layer slurry.
[0143] (2) Weigh 100 parts of silicon carbide powder, 8 parts of alumina, 10 parts of yttrium oxide and 1 part of flake alumina according to the internal mass ratio of the second silicon carbide mixed powder, and mix them to obtain the second silicon carbide mixed powder.
[0144] Based on a total mass of 100 parts by mass of the interface layer slurry, 38 parts by mass of the second silicon carbide mixed powder, 60 parts by mass of the photosensitive resin, 1.4 parts by mass of polypropylene glycol, and 0.6 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 3:1. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the second liquid phase composition. The second silicon carbide mixed powder and the second liquid phase composition were ball-milled at 200 rpm for 4 h to obtain the interface layer slurry.
[0145] (3-5) Following the steps (3-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 7 was obtained.
[0146] Comparative Example 8
[0147] The difference between the silicon carbide ceramic sample of Comparative Example 8 and Example 1 is that only the interface layer slurry prepared in step (2) of Example 1 was used for 3D photopolymerization printing. No matrix layer slurry was prepared, and the matrix layer slurry and interface layer slurry were not printed alternately. The other steps were the same as in Example 1.
[0148] (1) Preparation of single silicon carbide slurry: Weigh 100 parts of silicon carbide powder, 8 parts of alumina powder, 10 parts of yttrium oxide and 1 part of sheet graphene by mass, mix them evenly to obtain ceramic mixed powder.
[0149] Based on a total mass of 100 parts by weight of single silicon carbide slurry, 38 parts by weight of ceramic mixed powder, 60 parts by weight of photosensitive resin, 1.4 parts by weight of polypropylene glycol, and 0.6 parts by weight of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin consisted of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate. The above raw materials were placed in a ball mill jar and ball-milled at 200 rpm for 4 hours to obtain the single silicon carbide slurry.
[0150] (2) 3D photopolymerization printing: Establish a three-dimensional CAD model of the ceramic sample, set the layer parameters and scanning path data, pour the single silicon carbide slurry obtained in step (1) into the liquid tank of the DLP printer, import the 3D model data, set the intensity of the ultraviolet light source to 20 mW / cm2, the curing time of a single layer to 4 s, the curing thickness of a single layer to 12 μm, and print layer by layer to obtain a uniform structure ceramic blank.
[0151] (3) Drying, degreasing and sintering: The uniform ceramic green body obtained in step (2) is dried at 110℃ for 12 h, and then placed in a nitrogen atmosphere and heated to 800℃ at a heating rate of 0.25℃ / min for degreasing treatment to obtain the degreased ceramic green body.
[0152] The degreased ceramic green body was embedded in high-purity silicon powder and heated to 1700℃ at a heating rate of 1.5℃ / min. It was then held at 1700℃ for 4 h to carry out silicon-embedded reaction sintering, thus obtaining the silicon carbide ceramic sample of Comparative Example 8.
[0153] Comparative Example 9
[0154] The difference between the silicon carbide ceramic sample of Comparative Example 9 and Example 1 is that in step (3), instead of using a scraper to spread the slurry layer by layer along the forming surface direction, a quantitative feeding method followed by static leveling is used to form the slurry layer to be cured. The other steps are the same as in Example 1:
[0155] (1-2) Following the steps (1-2) of Example 1, the matrix layer slurry and the interface layer slurry are obtained respectively.
[0156] (3) Establish a three-dimensional CAD model of the ceramic component to be prepared, set the layering parameters and scanning path, and place the matrix layer slurry and interface layer slurry in different liquid tanks of the DLP printing equipment. During the layer-by-layer printing process, instead of using a scraper to spread the matrix layer slurry or interface layer slurry to be printed along the forming layer direction, the matrix layer slurry or interface layer slurry to be printed is quantitatively added to the forming area, and the thickness of the slurry layer to be cured is controlled by adjusting the distance between the forming platform and the liquid surface. After standing and leveling for 3 seconds, 3D photocuring is performed for alternating layer-by-layer printing, so that the matrix layer slurry and interface layer slurry are cured to form matrix layers and interface layers that are alternately arranged along the thickness direction. One matrix layer and one interface layer constitute a set of layered repeating units, and a total of 600 sets of layered repeating units are printed along the thickness direction. The intensity of the ultraviolet light source used for the matrix layer slurry is 18mW / cm. 2 The curing time for a single layer is 10 s, and the curing thickness of a single layer is 40 μm; the intensity of the ultraviolet light source used for the interface layer slurry is 20 mW / cm². 2 The curing time for a single layer was 4 s, and the curing thickness of a single layer was 12 μm, resulting in a ceramic green body.
[0157] (4-5) Following the steps (4-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 9 was obtained.
[0158] Comparative Example 10
[0159] The difference between the silicon carbide ceramic sample of Comparative Example 10 and Example 1 lies in the thickness of the sheet graphene in step (2), while the other steps are the same as in Example 1:
[0160] (1) Follow the steps (1) of Example 1 to obtain the matrix layer slurry.
[0161] (2) Weigh 100 parts of silicon carbide powder, 8 parts of alumina, 10 parts of yttrium oxide and 1 part of sheet graphene according to the internal mass ratio of the second silicon carbide mixed powder, and mix them to obtain the second silicon carbide mixed powder. The average sheet diameter of the sheet graphene is 3 μm and the thickness is 800 nm.
[0162] Based on a total mass of 100 parts by mass of the interface layer slurry, 38 parts by mass of the second silicon carbide mixed powder, 60 parts by mass of the photosensitive resin, 1.4 parts by mass of polypropylene glycol, and 0.6 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 2:1. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the second liquid phase composition. The second silicon carbide mixed powder and the second liquid phase composition were ball-milled at 200 rpm for 4 h to obtain the interface layer slurry.
[0163] (3-5) Following the steps (3-5) of Example 1, a silicon carbide ceramic sample of Comparative Example 10 was obtained.
[0164] Comparative Example 11
[0165] The difference between the silicon carbide ceramic sample of Comparative Example 11 and Example 1 lies in the thickness of the sheet graphene in step (2), while the other steps are the same as in Example 1:
[0166] (1) Follow the steps (1) of Example 1 to obtain the matrix layer slurry.
[0167] (2) Weigh 100 parts of silicon carbide powder, 8 parts of alumina, 10 parts of yttrium oxide and 1 part of sheet graphene according to the internal mass ratio of the second silicon carbide mixed powder, and mix them to obtain the second silicon carbide mixed powder. The average sheet diameter of the sheet graphene is 3 μm and the thickness is 50 nm.
[0168] Based on a total mass of 100 parts by mass of the interface layer slurry, 38 parts by mass of the second silicon carbide mixed powder, 60 parts by mass of the photosensitive resin, 1.4 parts by mass of polypropylene glycol, and 0.6 parts by mass of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were weighed. The photosensitive resin was composed of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 2:1. The photosensitive resin, polypropylene glycol, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide constituted the second liquid phase composition. The second silicon carbide mixed powder and the second liquid phase composition were ball-milled at 200 rpm for 4 h to obtain the interface layer slurry.
[0169] (3-5) Following the steps (3-5) of Example 1, the silicon carbide ceramic sample of Comparative Example 11 was obtained.
[0170] The silicon carbide ceramic samples prepared in Examples 1-3 and Comparative Examples 1-11 were subjected to performance tests, and the test methods are as follows:
[0171] The fracture toughness test method is as follows: The single-sided pre-cracked beam method in GB / T 23806-2009 is used for testing. The samples are processed into specimens with dimensions of 2×4×20 mm, the test span is 16 mm, the loading speed is 0.05 mm / min, and the fracture toughness of each specimen is measured.
[0172] The bending strength test method is as follows: The three-point bending method in GB / T 6569-2006 is used for testing. The samples are processed into specimens with dimensions of 3×4×36 mm, the test span is 20 mm, the loading speed is 0.5 mm / min, and the bending strength of each specimen is measured.
[0173] The microstructure observation method is as follows: The hierarchical layered silicon carbide ceramic green body prepared in Example 1 was cut along the direction perpendicular to the printed layer to obtain a cross-sectional sample that allows observation of the alternating arrangement of the matrix layer and the interface layer. The cross-sectional sample was then sequentially inlaid, ground, polished, cleaned, and dried. The observation surface was then subjected to gold or carbon spraying for conductivity. The microstructure of the cross-sectional sample was observed using a scanning electron microscope to obtain a microscopic morphology image of the cross-section of the hierarchical layered silicon carbide ceramic green body. The observation results are shown in [the table below]. Figure 2 .
[0174] The sintered hierarchical layered silicon carbide ceramic sample prepared in Example 1 was cut along the direction perpendicular to the printed layer to expose the interface layer region. After grinding, polishing, cleaning, drying, and conductive treatment, the microstructure of the interface layer region was observed using a scanning electron microscope, and the scanning electron microscope image of the interface layer region was obtained. The observation results are shown in […]. Figure 3 .
[0175] The interface layer region of the sintered hierarchical layered silicon carbide ceramic sample prepared in Example 1 was observed using a high-magnification scanning electron microscope. The focus was on observing the morphology of the layered silicon carbide formed by the embedded silicon reaction sintering of sheet graphene within the interface layer. Scanning electron microscope images of the layered silicon carbide were obtained, and the observation results are shown in [Figure 1]. Figure 4 .
[0176] Table 1 Performance test results of silicon carbide ceramic samples obtained in Examples 1-3 and Comparative Examples 1-11
[0177]
[0178] Depend on Figure 2 It can be seen that the cross-section of the hierarchical layered silicon carbide ceramic green body prepared in Example 1 shows a continuous layered arrangement structure, indicating that by using matrix layer slurry and interface layer slurry for 3D photocuring alternating printing, a ceramic green body with a clear layered structure can be obtained.
[0179] Depend on Figure 3 and Figure 4 It can be seen that the hierarchical layered silicon carbide ceramic interface layer region prepared in Example 1 has a sheet-like structure, and the sheet-like structure exhibits a sheet-like morphology under a high-magnification scanning electron microscope, indicating that the sheet-like graphene in the interface layer can be transformed into sheet-like silicon carbide that maintains the sheet-like morphology and has an internal layered structure during the buried silicon reaction sintering process.
[0180] As shown in Table 1, the graded layered silicon carbide ceramics obtained in the embodiments of the present invention all have good fracture toughness and flexural strength, indicating that by alternating the construction of the matrix layer and the interface layer, the orientation distribution of the sheet-like powder, and the localization introduction of sheet-like graphene in the interface layer, the crack propagation resistance and overall load-bearing capacity of silicon carbide ceramics can be effectively improved.
[0181] By comparing Example 1 and Example 2, it can be seen that after replacing the first flaky powder in the matrix layer with flaky alumina, the material can still maintain good mechanical properties, indicating that flaky alumina can also participate in crack control, but flaky boron nitride has a better synergistic effect with this system.
[0182] By comparing Example 1 and Example 3, as well as Comparative Examples 1 to 3, it can be seen that the thickness ratio of the matrix layer to the interface layer affects the control effect of the interlayer structure on the crack propagation path. When the interface layer is too thick, the interlayer functional zoning is weakened; when the interface layer is too thin, the crack control area is insufficient. Both are not conducive to the comprehensive improvement of the material's toughness and strength.
[0183] By comparing Example 1 and Comparative Example 4, it can be seen that after replacing the sheet graphene in the interface layer with carbon black, although it can still provide a carbon source for the reaction, it is difficult to form a sheet silicon carbide structure with sheet morphology and internal layered structure, resulting in crack deflection, bifurcation and weakening of bridging effect.
[0184] By comparing Example 1 and Comparative Example 5, it can be seen that printing after mixing the matrix layer slurry and the interface layer slurry cannot form a stable and clear alternating layered structure. This indicates that the performance improvement of the present invention does not simply come from the superposition of components, but depends on the orderly construction of the layered structure.
[0185] By comparing Example 1 and Comparative Example 6, it can be seen that after the sheet graphene is dispersed and added to the matrix layer and the interface layer, the enrichment degree of the sheet silicon carbide structure in the interface layer is reduced, and the interface layer's ability to centrally control the crack propagation path is weakened.
[0186] By comparing Example 1 and Comparative Example 7, it can be seen that although sheet-like alumina has a certain sheet-like reinforcing effect when used as an interface layer, it cannot be transformed into a sheet-like silicon carbide structure with an internal layered structure during the buried silicon reaction sintering process. Therefore, the interface toughening effect is weaker than that of sheet-like graphene.
[0187] By comparing Example 1 and Comparative Example 8, it can be seen that when printing with only a single silicon carbide slurry containing sheet graphene, the lack of partitioning between the matrix layer and the interface layer, as well as the localized toughening structure of the interface layer, makes it difficult to obtain the hierarchical layered toughening effect of the present invention.
[0188] By comparing Example 1 and Comparative Example 9, it can be seen that when the sheet powder is not spread layer by layer without the use of a scraper, the orientation effect of the sheet powder along the layer direction is weakened, and the crack deflection and bridging effects are reduced.
[0189] By comparing Example 1 with Comparative Examples 10 and 11, it can be seen that both excessively large and excessively small thicknesses of sheet graphene are not conducive to the stable construction of sheet-like toughened structures in the interface layer. When the thickness is too large, the dispersion and orientation effects deteriorate, while when the thickness is too small, agglomeration or morphological damage is likely to occur, both of which weaken the overall mechanical properties of the material.
[0190] The above results indicate that the present invention, through the synergistic combination of layered structure design, sheet powder orientation, localized distribution of sheet graphene, and its reaction transformation structure, makes it easier for cracks to deflect, bifurcate, and bridge during crack propagation, thereby improving the fracture toughness and structural reliability of silicon carbide ceramics.
[0191] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A method for preparing hierarchical layered silicon carbide ceramics, characterized in that, Includes the following steps: (1) A first silicon carbide mixed powder with a mass ratio of 3:7 to 11:9 is mixed with a first liquid phase composition to obtain a matrix layer slurry; (2) The second silicon carbide mixed powder with a mass ratio of 3:7 to 2:3 is mixed with the second liquid phase composition to obtain an interface layer slurry; (3) The substrate slurry and the interface slurry are spread layer by layer using a scraper, and then 3D photocuring is performed to print layer by layer alternately to form at least one hundred layered repeating units. Each layered repeating unit includes a substrate layer and an interface layer arranged alternately along the thickness direction to obtain a graded layered ceramic blank. (4) The graded layered ceramic green body is dried and degreased to obtain a degreased ceramic green body; (5) The degreased ceramic blank is embedded in silicon powder and sintered under vacuum at 1650-1750℃ to obtain graded layered silicon carbide ceramic. Wherein, the first silicon carbide mixed powder includes silicon carbide and a first sheet-like powder, wherein the first sheet-like powder is any one or two of sheet-like boron nitride and sheet-like alumina. In the first silicon carbide mixed powder, the first flake powder is 1-3 parts by weight, with silicon carbide as 100 parts by weight; The second silicon carbide mixed powder comprises silicon carbide and sheet-like graphene; In the second silicon carbide mixed powder, based on 100 parts by mass of silicon carbide, the sheet-like graphene comprises 0.5-2 parts by mass; The thickness of the sheet-like graphene is 100-400 nm, and the average sheet diameter is 2-5 μm; Both the first liquid phase composition and the second liquid phase composition contain a photosensitive resin, a dispersant, and a photoinitiator; In any of the layered repeating units, the thickness ratio of the matrix layer to the interface layer is (2-5):
1.
2. The preparation method according to claim 1, characterized in that, In step (1), the first silicon carbide mixed powder further includes aluminum oxide and yttrium oxide; based on 100 parts by mass of silicon carbide in the first silicon carbide mixed powder, the aluminum oxide is 4-8 parts by mass and the yttrium oxide is 6-12 parts by mass. In step (2), the second silicon carbide mixed powder further includes aluminum oxide and yttrium oxide; based on 100 parts by mass of silicon carbide in the second silicon carbide mixed powder, the aluminum oxide is 4-8 parts by mass and the yttrium oxide is 6-12 parts by mass.
3. The preparation method according to claim 1, characterized in that, In step (1), the photosensitive resin in the first liquid phase composition is any one or more of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, bisphenol A epoxy acrylate, toluene 2,4-diisocyanate and hydroxyethyl acrylate. And / or, in step (1), the dispersant in the first liquid phase composition is any one or more of polypropylene glycol, polyphosphate ester and modified acrylic copolymer; And / or, in step (1), the photoinitiator in the first liquid phase composition is any one or more of diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methylphenylacetone and 1-hydroxycyclohexylphenyl ketone; And / or, in step (2), the photosensitive resin in the second liquid phase composition is any one or more of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, bisphenol A epoxy acrylate, toluene 2,4-diisocyanate and hydroxyethyl acrylate; And / or, in step (2), the dispersant in the second liquid phase composition is any one or more of polypropylene glycol, polyphosphate ester and modified acrylic copolymer; And / or, in step (2), the photoinitiator in the second liquid phase composition is any one or more of diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methylpropionone, and 1-hydroxycyclohexylphenyl ketone.
4. The preparation method according to claim 3, characterized in that, In step (1), the photosensitive resin in the first liquid phase composition is 1,6-hexanediol diacrylate and trimethylolpropane triacrylate, and the volume ratio of the 1,6-hexanediol diacrylate to the trimethylolpropane triacrylate is (5-8):(1-4). And / or, in step (2), the photosensitive resin in the second liquid phase composition is 1,6-hexanediol diacrylate and trimethylolpropane triacrylate, and the volume ratio of the 1,6-hexanediol diacrylate to the trimethylolpropane triacrylate is (5-8):(1-4).
5. The preparation method according to claim 1, characterized in that, In step (1), based on a total mass of 100 parts by mass of the first silicon carbide mixed powder, photosensitive resin, dispersant and photoinitiator in the matrix layer slurry, the first silicon carbide mixed powder is 30-55 parts by mass, the dispersant is 0.5-3 parts by mass, the photoinitiator is 0.1-1 parts by mass, and the photosensitive resin is the balance. And / or, in step (2), based on a total mass of 100 parts by mass of the second silicon carbide mixed powder, photosensitive resin, dispersant and photoinitiator in the interface layer slurry, the second silicon carbide mixed powder is 30-40 parts by mass, the dispersant is 0.5-2 parts by mass, the photoinitiator is 0.1-1 parts by mass, and the photosensitive resin is the balance.
6. The preparation method according to claim 1, characterized in that, In step (1), the mixing of the first silicon carbide mixed powder and the first liquid phase composition is ball milling; In step (2), the mixing of the second silicon carbide mixed powder and the second liquid phase composition is ball milling.
7. The preparation method according to claim 6, characterized in that, In step (1), the ball milling speed of the first silicon carbide mixed powder and the first liquid phase composition is 200-400 rpm, and the ball milling time is 5-10 h; And / or, in step (2), the ball milling speed of the second silicon carbide mixed powder and the second liquid phase composition is 150-300 rpm, and the ball milling time is 3-6 h.
8. The preparation method according to claim 1, characterized in that, In step (3), during the alternating layer-by-layer 3D photocuring printing, the intensity of the ultraviolet light source used for the substrate slurry is 10-30 mW / cm². 2 The curing time for a single layer is 9-20 seconds; And / or, in step (3), the intensity of the ultraviolet light source used for the interface layer slurry is 10-20 mW / cm². 2 The curing time for a single layer is 4-6 seconds.
9. The preparation method according to claim 1, characterized in that, In step (4), the drying temperature is 80-120℃; And / or, in step (4), the drying time is 10-20 hours; And / or, in step (4), the degreasing is carried out under a nitrogen protective atmosphere; And / or, in step (4), the heating rate for degreasing is 0.1-0.3℃ / min; And / or, in step (5), the reaction sintering time is 1-4 h.
10. A hierarchical layered silicon carbide ceramic, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.